2011
DOI: 10.1371/journal.pone.0017745
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Plasma MiR-141 Is a Novel Biomarker for Metastatic Colon Cancer and Predicts Poor Prognosis

Abstract: BackgroundColorectal cancer (CRC) remains one of the major cancer types and cancer related death worldwide. Sensitive, non-invasive biomarkers that can facilitate disease detection, staging and prediction of therapeutic outcome are highly desirable to improve survival rate and help to determine optimized treatment for CRC. The small non-coding RNAs, microRNAs (miRNAs), have recently been identified as critical regulators for various diseases including cancer and may represent a novel class of cancer biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
295
2
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(312 citation statements)
references
References 23 publications
6
295
2
9
Order By: Relevance
“…15 In summary, this study sheds light on a group of miRNAs that are altered in TET and are emerging as putative non-invasive biomarkers for TET management. These findings might be useful to pave the way for additional and more detailed investigations to clarify the clinical usefulness of circulating miRNAs in TET.…”
Section: Discussionmentioning
confidence: 87%
“…15 In summary, this study sheds light on a group of miRNAs that are altered in TET and are emerging as putative non-invasive biomarkers for TET management. These findings might be useful to pave the way for additional and more detailed investigations to clarify the clinical usefulness of circulating miRNAs in TET.…”
Section: Discussionmentioning
confidence: 87%
“…Many studies have been performed to quantify miRNAs in the blood for use as a biomarker (Table 4) [77][78][79][80][81][82][83][84][85][86][87][88] . miR-92a, located on chromosome 13q13, is a member of the miR-17-92 gene cluster.…”
Section: Mirna Biomarkers In Bloodmentioning
confidence: 99%
“…In these studies, miR-221 and miR-21 were upregulated in the plasma of CRC patients compared to healthy controls [79,83] , while miR-601 and miR-760 were down-regulated [78] . Moreover, a study conducted in two independent CRC cohorts suggested that high levels of plasma miR-141 could predict poor survival, and thus miR-141 may serve as an independent prognostic factor for advanced CRC patients [81] .…”
Section: Markersmentioning
confidence: 99%
“…Recent data have shown that miR-141 and miR-200c play important roles in tumorigenesis. For example, miR-141 increases in ovarian cancer (20) and colon cancer (21) and acts as an oncogene. Other researches show miR-141 is downregulated in renal cell carcinoma (22), breast cancer (23), and pancreatic cancer (24), and can inhibit cell growth in gastric cancer (25).…”
Section: Introductionmentioning
confidence: 99%